Spacecraft converge on Mars. - Digregorio, B.E.
The mystery of whether there is or has been life on Mars may be clarified or even resolved soon, with four new spacecraft-two from the European Space Agency and two from NASA-arriving at the planet. They join two NASA probes already in orbit, though one of them-Odyssey-had a radiation sensor knocked out by the unusually intense solar storms in October.
Keywords: European Space Agency; Mars Exploration Rovers; NASA probes; Odyssey; Life on Mars; Life sciences landers; Spacecraft converge